A Critical Discourse Analysis of the Use of Metaphor in Online Car Advertisements - Hartati, Rita; Panah, Ebrahim; Matsom, Hafizan (Association of Language Teachers in Southeast Asia (ALTSA), 2021)
The objectives of the current study are threefold: a) to investigate what types of metaphors are used in Arab and Western car advertisements and why they use them, b) to explore how metaphors are used in Arab and Western car advertisements, and c) to explore how cultural attributes are used along with metaphors in Arab and Western car advertisements. The study adopted a descriptive approach through content analysis using three models: cultural (Hofstede, 2005), metaphorical (Lankoff & Johnson, 1980), and contrastive discourse analysis (Farclough's, 2001), approaches to analyze the data. The study sample comprised 30 car advertisements from Holland, France, Germany, Italy, the US, and Arab countries, each with five advertisements published online in 2016. The findings of the study show that car advertisements frequently use metaphorical strategies. In addition, the study revealed differences between Arab and Western advertisements in terms of the employment of cultural attributes. Finally, the study also indicated that even within the Western context, there is a different use of metaphorical strategies with subtle differences.